19 The prevalence of elevated natriuretic peptide in a diabetic population without a history of heart failure. (28th September 2016) - O'Carroll, G; Harkins, V; Gallagher, J; James, S; O'Connell, E; Ledwidge, M; Watson, C; McDonald, K
Abstract : Purpose: Patients with diabetes are at increased risk of several cardiovascular disorders including heart failure. The objective of this study is to determine the prevalence of elevated natriuretic peptide (NP) in a diabetic population, characterise diabetics with normal and elevated NP levels, and examine the association between NP and heart failure in this population to allow appropriate structuring of heart failure prevention services. Methods: Patients enrolled in the HSE Midland Diabetes Structured Care Programme between May 2013 and Feb 2015 were included in this study. We measured the NP level of all participants and examined the characteristics of those with normal and elevated NP levels. We also determined the presence of heart failure in the elevated NP group using specific echocardiographic parameters (Table 1 ). Results: There were 611 patients with diabetes who had an NTproBNP level measured (58.6 % male, mean age 65.6 yrs). Two hundred and six patients (33.7%) had an NP level >125 pg/ml. Those with an elevated NP (>125 pg/ml) had higher rates of atrial fibrillation (18% vs 0.74%), HTN (51.5% vs 32.1%) and hyperlipidaemia (35.9% vs 25.4%) compared with the normal NP group. The use of Angiotensin receptor blockers (27% vs 18.9%), loop diuretics (25.8% vs 3.9%) and B blockers (50% vs 16.8%) was higher in the elevated NP group. The rate of hypoglycaemic medication use between the two groups was higher in the normal NP group (63.2 vs 54.5%). Thiazolidenedione use was higher in the high NP group (7.9% vs 3.9%).The median HbA1C level was 47 (42–55) with no significant difference between the groups. Baseline echocardiography was performed in 170 patients. Twenty patients (11.7%) had LV systolic dysfunction (LVSD, EF <50%) and 68 (49.6%) had LV diastolic dysfunction (LVDD, LAVI >34). An NP level >250 pg/ml was most predictive of the presence of LV dysfunction (LVSD 16.9%, LVDD 64.2%). Conclusions: Diabetic patients had a high prevalence of elevated NP. There was a high prevalence of LV dysfunction in those with elevated NP. Interval NP screening of this at risk population should be considered as part of the approach in reducing cardiovascular morbidity.